Effects of Occupational Fatigue on Cognitive Performance of Staff From a Train Operating Company: A Field Study - Fan, Jialin; Smith, Andrew P. (Frontiers in Psychology, 2020)
Background: Occupational fatigue is a key issue in the rail industry that can endanger staff, passenger, and train safety. There is a need to demonstrate the relationship between workload, fatigue, and performance among rail staff. Objective: The present study, conducted in the workplace in realistic situations, integrating both subjective and objective measurements, aimed to demonstrate the relationship between workload, fatigue, and cognitive performance with a rail staff sample. Methods: The “After-Effect” technique was applied in the current study. Online diaries and cognitive performance tasks were used to assess the fatigue, work experiences, and performance of rail staff before and after work on the first and last days of one working week. Results: Reported fatigue was greater after work on both the first and last day of the working week. There were large individual differences in the change in fatigue and workload ratings. Analyses of covariance with age and the pre-work performance score as covariates and the post-work performance score as the dependent variable showed that high levels of fatigue were associated with impaired performance on both the visual search and logical reasoning tasks. Workload had fewer effects on performance than fatigue. Conclusions: This field study provided evidence for the relationship between work-related fatigue and performance impairment. The findings show the need for future work on predicting fatigue-related performance decrements, and the necessity of providing interventions and support so that the risk to safety can be reduced.